2020
DOI: 10.1002/jgm.3233
|View full text |Cite
|
Sign up to set email alerts
|

Serum lncRNA LOXL1‐AS1 is a diagnostic and prognostic marker for epithelial ovarian cancer

Abstract: Background: The present study aimed to examine the levels of circulating LOXL1-AS1 in epithelial ovarian cancer (EOC) patients and to analyze its diagnostic and prognostic value. Methods: The levels of LOXL1-AS1 in 185 EOC patients and 43 healthy volunteers were evaluated by a quantitative reverse transcriptase-polymerase chain reaction. The potential of LOXL1-AS1 as a biomarker for EOC diagnosis was determined by receiver-operating characteristic (ROC) curve assays. The associations between clinicopathologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…Biomarkers identified in patients with advanced disease are not necessarily relevant for the early disease setting. The diagnostic performance of LOXL1-AS1, a potential biomarker identified in a cohort of 119 earlystage patients, 67 advanced patients and 43 healthy women, is clearly higher in patients with advanced disease compared to patients with early-stage disease [45]. However, we cannot exclude that some current or future biomarkers may exist that are useful for identification of both early and advanced disease, albeit with different sensitivity.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Biomarkers identified in patients with advanced disease are not necessarily relevant for the early disease setting. The diagnostic performance of LOXL1-AS1, a potential biomarker identified in a cohort of 119 earlystage patients, 67 advanced patients and 43 healthy women, is clearly higher in patients with advanced disease compared to patients with early-stage disease [45]. However, we cannot exclude that some current or future biomarkers may exist that are useful for identification of both early and advanced disease, albeit with different sensitivity.…”
Section: Discussionmentioning
confidence: 88%
“…In 14 out of the 36 studies age-matching between cases and controls was applied. In two studies, gender nor age of the control group was reported [38,45]. Samples of ovarian cancer patients with FIGO stage I-II are most interesting to investigate in the context of early detection.…”
Section: Risk Of Bias Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have revealed lncRNA dysregulation in a wide variety of human cancers and have identi ed lncRNAs as modulators of tumor etiology and progression [12][13][14]. Regarding EOC, a substantial amount of evidence has established that various lncRNAs are differentially expressed and function as tumor-inhibiting or tumor-promoting factors in regulating tumorigenesis [15][16][17]. microRNAs (miRNAs) are a class of single-stranded, non-coding RNA transcripts comprising [17][18][19][20][21][22][23][24] nucleotides [18].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have revealed lncRNA dysregulation in a wide variety of human cancers and have identi ed lncRNAs as modulators of tumor etiology and progression [12][13][14]. With regard to EOC, a substantial amount of evidence has established that a variety of lncRNAs are differentially expressed and function as tumor-inhibiting or tumor-promoting factors in regulating tumorigenesis [15][16][17]. microRNAs (miRNAs) are a class of single-stranded, non-coding RNA transcripts with a length of [17][18][19][20][21][22][23][24] nucleotides [18].…”
Section: Introductionmentioning
confidence: 99%